2006
DOI: 10.1128/aem.00830-06
|View full text |Cite
|
Sign up to set email alerts
|

The AauR-AauS Two-Component System Regulates Uptake and Metabolism of Acidic Amino Acids in Pseudomonas putida

Abstract: Pseudomonas putida KT2440 metabolizes a wide range of carbon and nitrogen sources, including many amino acids. In this study, a 54 -dependent two-component system that controls the uptake and metabolism of acidic amino acids was identified. The system (designated aau, for acidic amino acid utilization) involves a sensor histidine kinase, AauS, encoded by PP1067, and a response regulator, AauR, encoded by PP1066. aauR and aauS deletion mutants were unable to efficiently utilize aspartate (Asp), glutamate (Glu),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…The genome of Pseudomonas contains a large number of two-component regulatory systems (.60 sensorregulator pairs per genome; Kiil et al 2005), which play a major role in detecting niche-specific signals, including nutrient availability (Monds et al 2006;Sonawane et al 2006). Previous studies on histidine utilization (as the sole source of carbon and nitrogen) showed that CbrAB was required for hut activation in P. aeruginosa (Nishijyo et al 2001) and in P. fluorescens (Zhang and Rainey 2007); more recently evidence was obtained from a suppressor analysis of a cbrAB mutant for the involvement of a second two-component system, NtrBC (Itoh et al 2007;Li and Lu 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The genome of Pseudomonas contains a large number of two-component regulatory systems (.60 sensorregulator pairs per genome; Kiil et al 2005), which play a major role in detecting niche-specific signals, including nutrient availability (Monds et al 2006;Sonawane et al 2006). Previous studies on histidine utilization (as the sole source of carbon and nitrogen) showed that CbrAB was required for hut activation in P. aeruginosa (Nishijyo et al 2001) and in P. fluorescens (Zhang and Rainey 2007); more recently evidence was obtained from a suppressor analysis of a cbrAB mutant for the involvement of a second two-component system, NtrBC (Itoh et al 2007;Li and Lu 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As judged by sequence similarity, the response regulator AauR is a DNA-binding helix-turnhelix protein belonging to the Fis family (Morett & Bork, 1998). We have further shown that expression of aat depends on s 54 , an alternative sigma factor typically involved in the transcription of genes related to nitrogen metabolism (Sonawane et al, 2006).…”
Section: Introductionmentioning
confidence: 82%
“…Genes aatP (PP1068) and aatJ (PP1071) were inactivated by a strategy described previously in detail (Sonawane et al, 2006). Briefly, internal gene fragments of about 300 bp were amplified from the KT2440 genome using primers that introduce single base-pair frameshifts and cloned into pK18, a suicide vector that cannot multiply inside P. putida unless integrated into the genome by homologous recombination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations